The physiology of the normal human breast: an exploratory study - Mills, Dixie; Gordon, Eva J.; Casano, Ashley; Lahti, Sarah Michelle; Nguyen, Tinh; Preston, Alex; Tondre, Julie; Wu, Kuan; Yanase, Tiffany; Chan, Henry; Chia, David; Esfandiari, Mahtash; et al. (Journal of physiology and biochemistry, 2011)
The physiology of the nonlactating human breast likely plays a key role in factors that contribute to the etiology of breast cancer and other breast conditions. Although there has been extensive research into the physiology of lactation, few reports explore the physiology of the resting mammary gland, including mechanisms by which compounds such as hormones, drugs, and potential carcinogens enter the breast ducts. The purpose of this study was to explore transport of exogenous drugs into ductal fluid in nonlactating women and determine if their concentrations in the fluid are similar to those observed in the breast milk of lactating women. We selected two compounds that have been well characterized during lactation, caffeine and cimetidine. Caffeine passively diffuses into breast milk, but cimetidine is actively transported and concentrated in breast milk. After ingestion of caffeine and cimetidine, 14 nonlactating subjects had blood drawn and underwent ductal lavage at five time points over 12 h to measure drug levels in the fluid and blood. The concentrations of both caffeine and cimetidine in lavage fluid were substantially less than those observed in breast milk. Our results support recent evidence that the cimetidine transporter is not expressed in the nonlactating mammary gland, and highlight intriguing differences in the physiology and molecular transport of the lactating and nonlactating breast. The findings of this exploratory study warrant further exploration into the physiology of the nonlactating mammary gland to elucidate factors involved in disease initiation and progression.